2017
DOI: 10.1080/09540105.2016.1272551
|View full text |Cite
|
Sign up to set email alerts
|

Development of a monoclonal antibody assay and a lateral flow strip test for the detection of paromomycin residues in food matrices

Abstract: A monoclonal antibody (MAb) was produced against paromomycin and used in the development of an immunoassay and a lateral flow strip test for the detection of paromomycin residues in food matrices. The MAb had 25.1% cross-reactivity with neomycin, but was insensitive to other aminoglycosides. Tested under optimized conditions in 0.01 M phosphate-buffered saline, the half maximum inhibitory concentration (IC 50 ) of the MAb was 0.61 ng/ml for paromomycin and 2.43 ng/ml for neomycin, with results obtained within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Similarly, few studies have reported NFS determination using high-performance liquid chromatography and/or liquid chromatography tandem mass spectrometry (Horie et al, 1991;Segawa & Ikeda, 2000;Tao et al, 2010). Critically, these methods cannot meet current legislative requirements, due to their relative low sensitivities, their time consuming and expensive, clean-up procedures and their sophisticated analytical instruments (Ge, Suryoprabowo, Zheng, & Kuang, 2017;Isanga et al, 2017;Lin et al, 2018;Liu, Suryoprabowo, Zheng, Song, & Kuang, 2017;Suryoprabowo, Liu, Peng, Kuang, & Xu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, few studies have reported NFS determination using high-performance liquid chromatography and/or liquid chromatography tandem mass spectrometry (Horie et al, 1991;Segawa & Ikeda, 2000;Tao et al, 2010). Critically, these methods cannot meet current legislative requirements, due to their relative low sensitivities, their time consuming and expensive, clean-up procedures and their sophisticated analytical instruments (Ge, Suryoprabowo, Zheng, & Kuang, 2017;Isanga et al, 2017;Lin et al, 2018;Liu, Suryoprabowo, Zheng, Song, & Kuang, 2017;Suryoprabowo, Liu, Peng, Kuang, & Xu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the development of immunoassays for small organic molecules, as well known, hapten design plays a significant role. However, for some molecules with super-low molecular weight or simple structure, the desired effect cannot be always achieved simply by altering the structure of hapten (Isanga et al, 2017;Luo et al, 2014;Romestand et al, 2010;Xu et al, 2013). At these cases, antibodies were always produced against the derivative but not the small analyte, which means that a pre-derivatisation of the small analyte is necessary prior to analysis.…”
Section: Hapten Design Synthesis and Characterisationmentioning
confidence: 99%
“…Even though it can simultaneously detect major ochratoxins, HPLC is expensive, time consuming, and unsuitable for on-site detection (Gu, Liu, Song, Kuang, & Xu, 2016;Liu, Suryoprabowo, Zheng, Song, & Kuang, 2017;Suryoprabowo, Liu, Peng, Kuang, & Xu, 2014). TLC, the national standard test method, is rarely used because of its low sensitivity and specificity (Isanga et al, 2017;Khaemba et al, 2016;Suryoprabowo, Liu, Peng, Kuang, & Xu, 2015).…”
Section: Introductionmentioning
confidence: 99%